Multifractal scaling properties of daily air temperature time series. (May 2017) - Kalamaras, N.; Philippopoulos, K.; Deligiorgi, D.; Tzanis, C.G.; Karvounis, G.
Highlights: Multifractal Detrended Fluctuation Analysis is applied to temperature time series. Τhe examined time series show multifractality and are long-term positive correlated. Multifractality is due to different long-range correlations for various fluctuations. Daily mean, maximum and minimum time series show the same multifractal behavior. Abstract: The aim of the current research study is to examine the scaling properties of the mean daily, maximum and minimum air temperature time series of a single coastal site, located at the island of Crete in Greece. The Multifractal Detrended Fluctuation Analysis (MF-DFA) is used to examine the time series long-term correlation and the singularity spectrum to estimate the multifractality degree. The analysis reveals that the daily temperature time series exhibit a multifractal behavior, are positive long-term correlated and that their multifractal structure is insensitive to local fluctuations with large magnitudes.